Analisis Evaluasi Miskonsepsi dan Pemahaman Konseptual dalam Pembelajaran IPA: Tinjauan Sistematis - Hajiriah, Titi Laily (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to identify and analyze misconceptions and conceptual understanding in science education through a systematic review. Misconceptions often hinder the correct understanding of scientific concepts. Using a constructivist approach, this study explores cognitive theories that explain the origins of misconceptions and effective strategies to overcome them. Using a systematic review and meta-analysis within the PRISMA framework. This study emphasizes the importance of evaluation tools such as multi-tier diagnostic tests and the Certainty of Response Index (CRI) to identify and correct misconceptions. Analyzing 37 articles revealed that diverse evaluation methods offer valuable insights into students' understanding and misconceptions, each with its own pros and cons. The study findings suggest that science education can diversify teaching methods, improve the quality of evaluation instruments, and integrate technology into learning to support evaluation and address misconceptions. Additional recommendations include teacher training, contextual curriculum development, and ongoing monitoring and evaluation to improve the quality of science education.